PUBLIC INFORMATION AND INFORMING THE PUBLIC: CAPACITIES OF LOCAL SELF-GOVERNMENT IN THE REPUBLIC OF SERBIA - Milenković, Dejan (National interest, 2024)
One of the constitutional and legal responsibilities of the local self-government (LSGs), i.e. municipalities and cities in the Republic of Serbia, is „taking care of public information“. Content-wise, this jurisdiction implies ensuring the right to public information through the media (local or others, including the rules on state aid and project financing, rules on public procurement, etc.). However, there is another significant side related to the functioning of local self-government, which involves „informing the public“. It is about the obligation of local self-government to „provide“ information to citizens at the local level, within the framework of work transparency and citizens' right to information, as well as the right established by the Constitution and laws. In this way, the public is informed about the work and procedures, as well as the implementation of certain public policies in the local self-government (e.g. through announcements about the work of LSG bodies, providing non-commercial audiovisual media services, issuing newsletters about the undertaken „actions“ etc.). This paper is focused on the research, based on a sample of 25 municipalities and cities in the Republic of Serbia, in which way LSGs in the Republic of Serbia provide information to citizens at the local level, apart from through the (local) media. The research should present whether LSGs in the Republic of Serbia: (1) have the organizational, personnel, and other capacities to take care of informing the public and (2) the ways and forms through which LSGs independently of registered (local) media provide information to the general public at the local level.
Keywords: public policies; public information; informing the public; local self-government; Republic of Serbia